Interfacial Effects Between Dental Impression and Die Materials and Their Role in the Internal Fit of Indirect Resin-Based Composite Restorations - Murillo Weissheimer; João Carlos S. N. Foly; Fabíola G. Carvalho; Eliseu A. Münchow (Dentistry Journal)
Background/Objectives: This study tested a method for evaluating the internal fit of indirect resin-based composite (RBC) restorations, as well as the influence of different combinations of impression and die materials on the reproducibility of the topography of teeth prepared for indirect RBC restoration. Methods: Bovine incisors received flattened and cavitated areas at the cervical and middle thirds of the buccal surface, respectively. The samples were randomly assigned to two groups according to the material used for impression taking (n = 5): irreversible hydrocolloid and polyvinyl siloxane (PVS). Die replicas were obtained with Type IV gypsum or elastomeric material. RBC restorations were fabricated through an indirect technique (test) and a direct-indirect technique as the control. The internal fit of restorations was assessed by measuring the cementation line thickness with a digital caliper (simulated cementation protocol with ultra-light PVS) and validated using scanning electron microscopy (SEM). Surface topography (Sa, Sq, and Sz) was analyzed via optical profilometry, and wettability was assessed through the water contact angle method. The data were analyzed using t-test, ANOVA, and Pearson correlation tests (α = 5%). Results: The simulated cementation resulted in internal gap values positively correlated to the values from SEM (R2 = 0.958; p = 0.0102). The internal gap of restorations was not significantly correlated with the discrepancies between the topography of the die and tooth substrate (p ≥ 0.067). The combination of irreversible hydrocolloid and gypsum resulted in restorations with the lowest cementation line thickness, although in terms of roughness, this combination was the only one that resulted in significant differences from the control (p ≤ 0.028). The internal mean gap values of restorations were significantly correlated to the cumulative wettability difference of materials used during impression taking, fabrication of die replica, and restoration build-up (R2 = 0.981; p = 0.003). Conclusions: The reproducibility of topographical characteristics of the tooth in the die replica did not affect the internal adaptation of indirect RBC restorations, whereas surface wettability of materials presented a more relevant effect on the overall gap formation. The simulated cementation technique tested in the study shows potential as a simpler, cost-effective, and non-destructive method for evaluating the adaptation of indirect RBC restorations.